Optimizing the properties of vulcanized compounds for foodstuff conveyor belts in industrial microwave per-heating - Limhengha, Suphatchakorn; Sriseubsai, Wipoo (My University, 2018)
This research finds a natural rubber-based material with good dielectric properties and low cost for a foodstuff conveyor belt (FCB) that can be heated with microwaves. For this purpose, epoxidized natural rubber-50 (ENR50) and standard Thai rubber 5L (STR5L) were mixed with a filler mixture of silica and magnesium carbonate. The FCB compound with filler (FCBcF) yielding the best vulcanization time, and the best mechanical, dielectric and dynamic properties, was selected for further study. The optimal FCBcF, ENR50:SiO2:MgCO3 (100:40:40) with microwave pre-heating at 2.45 GHz and 340 W for one minute before vulcanization, was well cross-linked and strongly converted the microwaves to heat. FCBcF also showed satisfactory mechanical properties with reduced cost of raw materials and reduced the curing time by 50% per round. The results demonstrate that pre-heating of FCBcF prior to vulcanization reduces the time and cost of fabricating FCBs, providing long-term economic and environmental benefits.
Keywords: Dielectric material; Foodstuff conveyor belt; Industrial microwave; Vulcanized compounds